1995
DOI: 10.1152/ajpcell.1995.268.1.c259
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytochrome P-450 reduces voltage-gated K+ currents in pulmonary arterial myocytes

Abstract: Cytochrome P-450 (P-450) is a NADPH-requiring and O2-dependent monooxygenase system. It is present in lung and has been postulated to act as an O2 sensor in hypoxic pulmonary vasoconstriction. To determine whether P-450 is involved in the regulation of voltage-gated K+ (KV) channel activity in pulmonary artery (PA) myocytes, we used the whole cell patch-clamp technique to evaluate the effects of P-450 inhibitors on KV channel currents (IKV) and membrane potential (Em). Bath application of the P-450 inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It has been suggested that metabolic regulation of K + currents is a primary mechanism of HPV [3,20,21] and the involvement of K Ca channels [14,15], voltage-dependent K + channels [1,17,18,[22][23][24][25] and ATP-dependent K + channels [16] has been proposed by different groups of investigators. All these proposals are speculative, however, and no experiment has successfully demonstrated whether, under physiological conditions, the modulation of a K + channel by a certain factor actually contributes to changes in PASMC membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that metabolic regulation of K + currents is a primary mechanism of HPV [3,20,21] and the involvement of K Ca channels [14,15], voltage-dependent K + channels [1,17,18,[22][23][24][25] and ATP-dependent K + channels [16] has been proposed by different groups of investigators. All these proposals are speculative, however, and no experiment has successfully demonstrated whether, under physiological conditions, the modulation of a K + channel by a certain factor actually contributes to changes in PASMC membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the cellular redox potential on Ca 2+ -activated K + (K Ca ) channels was found to be different between PAS-MC and EASMC. It was shown that a reducing agent markedly decreased K Ca channel activity only in PAS-MC, implying that this mechanism is responsible for the On the other hand, it was also shown that Kv current was decreased by reducing agents and it has been suggested that voltage-sensitive (Kv) current plays a key role in HPV [1,10,17,23,24]. However, the hypothesis that the Kv channel is involved has not yet been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary vascular remodeling or concentric vascular wall thickening of small pulmonary arteries (PAs) and arterioles, attributable partially to enhanced proliferation and migration of PA smooth muscle cells (PASMC), is a major cause for elevated PVR in patients with PAH and chronic hypoxia-induced pulmonary hypertension (HPH) (32,54,74). Multiple cellular and molecular mechanisms have been demonstrated to contribute to the development and progression of pulmonary vascular remodeling through enhanced PASMC proliferation and migration, such as signaling cascades involving intracellular free Ca 2ϩ (12,37,50,75), K ϩ channels (51,62,73), Notch (26,69), bone morphogenetic protein/transforming growth factor-␤ (38,42,48), and/or Akt/mammalian target of rapamycin (mTOR) (4,20,23); however, the specific sequence of events involved in the enhanced PASMC proliferation in pulmonary hypertension remains unclear.…”
mentioning
confidence: 99%
“…The incomplete (81%) inhibition by 50 nM ChTX might simply be due to its less-than-sufficient concentration to reach a full block of IK, because the IC 50 of the toxin was estimated to be ϳ30 nM for the IK in brain microvascular endothelial cells (Van Renterghem et al, 1995) and for the cloned human IK in HEK-293 cells (Jensen et al, 1998). The strong suppression by clotrimazole was probably not due to its inhibitory action on cytochrome P450 or voltage-gated K ϩ channels (Yuan et al, 1995;Eichler et al, 2003), since the AChinduced hyperpolarization was not affected by 17-octadecynoic acid, a known cytochrome P450 inhibitor (Jiang et al, 2005). In addition, the estimated IC 50 (116 nM) of clotrimazole is very close to that determined from HEK-293 cells that expressed human IK channels (153 nM; Jensen et al, 1998), and it is ϳ2-fold of that determined from the IK expressed in glioblastoma GL-15 cell lines (63 nM; Fioretti et al, 2004).…”
Section: Discussionmentioning
confidence: 99%